BENEFITS OF LEARNING A SECOND LANGUAGE - Zulfizar Qo'chqorova Abduxamid qizi; Shahnoza Solijonova Ikromjon qizi (TADQIQOTLAR.UZ, 2023)
Annotation: This article provides an in-depth exploration of the benefits of learning a second language, drawing on both existing research and a survey of bilingual individuals. It emphasizes the cognitive, academic, social, and cultural advantages of being bilingual and advocates for promoting multilingualism.